PHYLOGENETIC ANALYSIS OF ANTHROPOMORPHIC ROCK ART: A STUDY OF MATERIAL CULTURE EVOLUTION - Chair, Muhammad Faisal; Akbar, Ali (International Review of Humanities Studies, 2024)
This paper provides an explanation of the application of phylogenetic analysis, derived from biology, to be applied in archaeology with the aim of observing evolutionary phenomena, the development of ideas, and the dissemination of ideas from material culture. Phylogenetics will be applied to data on anthropomorphic motifs at five rock art sites in West Sumatra: Gua Lidah Air, Gua Runjo, Ngalau Tompok Syohiah, Batu Basurek, and Gua Basurek. The main stages in this analysis involve collecting representative data in the category of distinctive values from each rock art site. Distinctive values data is obtained through observation and identification of morphological characteristics, such as anthropomorphic postures, body shapes, foot patterns, hand patterns, attributes, and other morphologies, thus forming unique codes for each anthropomorphic rock art. This data is then analysed using phylogenetics to depict the relationships of anthropomorphic motifs at the five rock art sites in West Sumatra. The analysis results show similarities and differences in the depiction of anthropomorphic motifs among the rock art sites in West Sumatra, indicating the dissemination and development of ideas of anthropomorphic designs.